2009
DOI: 10.3168/jds.2008-1134
|View full text |Cite
|
Sign up to set email alerts
|

Herd-level risk factors for seven different foot lesions in Ontario Holstein cattle housed in tie stalls or free stalls

Abstract: Worldwide, there is considerable between-herd variation within individual foot lesion prevalence studies. This variation suggests that herd-level risk factors are important from a prevention perspective. The objective was to determine the effect of selected risk factors on the prevalence of 7 foot lesions in both tie-stall and free-stall housing systems. As part of a cross-sectional foot lesion study 5 hoof trimmers recorded lesions for all cows that were foot trimmed in a herd. In addition, they completed a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
3
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 24 publications
7
52
3
6
Order By: Relevance
“…This indicates that the beneficial effects of pasture access depend on the conditions of the outdoor area. Decreased risks of heel horn erosions, interdigital dermatitis and DD have been found when pasture grazing systems are compared with indoor systems or systems with access to outdoor exercise areas (Wells et al, 1999;Somers et al, 2005;Cramer et al, 2009). The common interpretation of this relationship is that the pasture-based system provides the best hygienic conditions and the results from this study support this theory.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This indicates that the beneficial effects of pasture access depend on the conditions of the outdoor area. Decreased risks of heel horn erosions, interdigital dermatitis and DD have been found when pasture grazing systems are compared with indoor systems or systems with access to outdoor exercise areas (Wells et al, 1999;Somers et al, 2005;Cramer et al, 2009). The common interpretation of this relationship is that the pasture-based system provides the best hygienic conditions and the results from this study support this theory.…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, it seems plausible that infectious diseases of the skin and hoof tissue can be caused by environmental pathogens and that unhygienic conditions may increase the prevalence by increasing the susceptibility of the skin, by amplifying the infection pressure, or both. The effect of different parameters affecting the cows' environment such as floor type, use of scrapers and access to outdoor paddocks have been evaluated in several studies indicating that poor hygienic conditions can be associated with an increased risk of digital dermatitis (DD) and heel horn erosions (Wells et al, 1999;Somers et al, 2005;Cramer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that short cleaning intervals considerably reduce manure on wa lkways and improve the cleanliness of dairy cattle and the housing environment [13,14,15]. This is inconsistent with the observations of Cramer et al [16] indicating that there was a negative relationship between the frequency of alley scraping and the prevalence of digital dermatit is. A previous study addressed hoof trauma caused by manure removing equip ment that may harm skin and horn barriers of the bovine feet [10].…”
Section: Introductioncontrasting
confidence: 57%
“…Lameness is widely recognized as a significant welfare problem for cows in free-stalls (von Keyserlingk et al, 2012) and tie-stalls (Bielfeldt et al, 2005;Cramer et 2009) caused by numerous factors including lying comfort, cubicle design, flooring type, time away from the pen for milking, body condition score (BCS), and nutrition Espejo and Endres, 2007). Hock and knee lesions are also common in cattle kept in tie-stalls (Zurbrigg et al, 2005), are more common among lame cattle (Zaffino Heyerhoff et al, 2014) and are also a common welfare concern (Rushen et al, 2008;von Keyserlingk et al, 2009).…”
Section: Introductionmentioning
confidence: 98%